DESKRIPSI METAKOGNISI SISWA SMA DALAM MEMECAHKAN MASALAH FISIKA MATERI GERAK LURUS - Tongena, Andrew Kurniawan; Werdhiana, I Komang (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aimed to describe the process of students' metacognition in solving physics problems on linear motion. The subjects of this study were 34 students of class XI IPA 5 SMA Negeri Model Terpadu Madani Palu. 6 respondents were selected from 34 students who represented high, medium and low category that consisted of 2 respondents each category. The selection of respondents was taken using purposive sampling technique. The data in this study were collected through observation, written essay tests and interviews. The research data were analyzed through a descriptive-qualitative approach. Based on the results of the analysis and conformity with metacognitive indicators, it showed that the high category students' metacognition fulfills all the problem-solving steps, so that the high category students are at the Reflective Use metacognitive level. Based on the results of the analysis and conformity with the metacognitive indicators, it showed that the students' metacognition in the medium and low categories have not fulfilled all the problem-solving steps, so that the middle and low category students are at the Aware Use metacognitive level.